Development of Concave-convex Tooth Chainless Traction Walking System of Shearer - Guang Wang (Jixie chuandong)
Abstract The rectangular coordinate equation of the concave-convex gear is established， the convex tooth surface is simulated by Matlab， the three-dimensional model of the gear-rail system is established according to the tooth profile， and the stress state is analyzed. The contact and bending strength are analyzed in Ansys software， and the kinematics performance is analyzed by Adams software. The analysis results show that the gear-rail system has good mechanical properties and strong adaptability. Through analysis and selection of the processing equipment of the complex tooth surface walking wheel， the problem of production and processing is solved. The practical performance of the system is verified by means of 3D printing， tooling test and industrial test. The test results show that the system reduces the contact strength of the walking part and improves the service life of the system.